Contemporary Asian Art and Exhibitions Connectivities and World-making - Antoinette, Michelle (ANU Press, 2014)
This volume draws together essays by leading art experts observing the dramatic developments in Asian art and exhibitions in the last two decades. The authors explore new regional and global connections and new ways of understanding contemporary Asian art in the twenty-first century.